3-D numerical study of offshore tripod wind turbine pile foundation on wave-induced seabed response. (1st July 2022) - Asumadu, Richard; Zhang, Jisheng; Osei-Wusuansa, Hubert
Abstract: Investigation analysis of wave-seabed-structure interaction (WSSI) is a pre-requisite in every marine engineering design and construction due to the huge failure of offshore structures every year, resulting in financial losses. In this study, an integrated 3-D numerical model is established to investigate the wave-induced oscillatory seabed response around the offshore substructure foundation of the tripod support pile. In the integrated numerical model, the Reynolds-Average Navier-Stokes (RANS) equations with k − ε turbulence closure model for the mean fluid flow is applied as the governed equation for the fluid computation, while the Biot consolidation equations are applied as the governing equation for the porous seabed substructure foundation model. The integrated numerical model is validated against physical experimental data from other previous works; to demonstrate that the present numerical model has the capability and capacity of simulating the WSSI around the offshore tripod pile structure foundation, which indicated good results. The results from the wave-induced liquefaction around the tripod support pile show that liquefaction depth at the offshore area and the lateral area of the upstream axillary pile leg tends to be larger than the two axillary pile legs at the lee area. Highlights: Offshore tripod pile turbine foundation for generating green energy. Seabed instability as result of wave-induced response. Wave-induced seabed response as result of wave-seabed-structure interaction (WSSI). Wave-induced liquefaction resulting from induce excess pore pressure. Effect of the axillary legs of the tripod pile on the wave-induced seabed response.